DIFFERENTIAL HABITAT SELECTION BY MOOSE AND ELK IN THE BESA-PROPHET AREA OF NORTHERN BRITISH COLUMBIA - Gillingham, Michael P; Parker, Katherine L (Lakehead University, 2008)
Elk (Cervus elaphus) populations are increasing in the Besa-Prophet area of northern British Columbia, coinciding with the use of prescribed burns to increase quality of habitat for ungulates. Moose (Alces alces) and elk are now the 2 large-biomass species in this multi-ungulate, multi-predator system. Using global positioning satellite (GPS) collars on 14 female moose and 13 female elk, remote-sensing imagery of vegetation, and assessments of predation risk for wolves (Canis lupus) and grizzly bears (Ursus arctos), we examined habitat use and selection. Seasonal ranges were typicallysmallest for moose during calving and for elk during winter and late winter. Both species used largest ranges in summer. Moose and elk moved to lower elevations from winter to late winter, but subsequent calving strategies differed. During calving, moose moved to lowest elevations of the year, whereas elk moved back to higher elevations. Moose generally selected for mid-elevations and against steep slopes; for Stunted spruce habitat in late winter; for Pine-spruce in summer; and for Subalpine during fall and winter. Most recorded moose locations were in Pine-spruce during late winter, calving, and summer, and in Subalpine during fall and winter. Elk selected for mid-elevations except in summer and for steep slopes in late winter. Use and selection of 3 habitat classes were prominent for elk: Deciduous and Elymus burns, and Subalpine. Highest overlap between moose and elk occurred during fall and winter when both species used and strongly selected for Subalpine habitat. Neither elk nor moose selected areas to minimize the risk of wolf predation, but elk selected areas with lower risk of predation by grizzly bears and higher vegetation quality during calving and summer.